Sources of local modern history as component of history of country: conservation problems and possibility of using - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The ratio of historical science and local history is not an object of scientific polemics. In the Russian scientific tradition, they exist as different branches of knowledge. Under the circumstances, local lore materials are valued when mentioning a particular local event in the context of the History of Russia and its concept. Local history materials serve as illustrations of the concepts of the concept. Meanwhile, the materials of local history can not only supplement and illustrate, but also make adjustments to the content of the historical narrative. This circumstance has special significance in relation to modern history, as it is closely intertwined with the socioeconomic and socio-political life of recent decades